(untitled) (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
Fundamental Law of Economics (FLoE). A finitely (not infinitely) converging algorithm addressing the dual market variables price and quantity simultaneously represents the mathematical formulation for the economic globalization of the planet. The document discusses the application of the Constructal Law and the Fundamental Law of Economics in addressing resistance to flow in economic systems, leading to the globalization of the planet.